Pengaruh Kecerdasan Emosional Dan Ethical Sensitivity Terhadap Persepsi Etis Mahasiswa Sebagai Calon Akuntan - Ridho Irmas Ferdian; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2020)
This study wanted to determine the ethical perceptions of students from the individual side of accounting students at FE UNP, namely from the emotional intelligence and ethical sensitivity of students. The author makes students the object of research because an accountant's ethical perceptions can also be influenced by several factors. One of them is external factors, namely the environment. The environment affects the formation of a person's character so that it affects their behavior. This research is classified as a causative research. The population used in this study were accounting students at the Padang City College. Samples were taken using purposive stratified sampling technique. Where is the sampling by taking samples of people selected by the author according to specific characteristics and certain characters. The analysis used in this study is multiple linear regression analysis used in this study is to use the SPSS 21 computer program. . The results of this study are that emotional intelligence has a positive effect on students' ethical perceptions as prospective accountants and ethical sensitivity has a positive effect on students' ethical perceptions as prospective accountants.